Pengaruh Komitmen Organisasional,Work Life Balance Dan Beban Kerja Terhadap Kinerja Pegawai Di Dinas Kebudayaan Kota Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
The performance of the State Civil Apparatus is always in the public spotlight as a form of control. Factors that can influence employee performance are organizational commitment, work-life balance, and workload. The purpose of this study is to determine the effect of organizational commitment, work-life balance, and workload on employee performance at the Denpasar City Cultural Office. This study was conducted at the Denpasar City Cultural Office, which has 45 employees and is the population in this study. All members of the population were involved as respondents using a census method. The results of the analysis show that partially organizational commitment and work-life balance have a positive and significant effect, while workload has a significant negative effect. Simultaneously, organizational commitment, work-life balance, and workload have a positive and significant effect simultaneously on employee performance at the Denpasar City Cultural Office. Suggestions given are improvements, especially on employee loyalty, which is demonstrated by loyalty to the Denpasar City Cultural Office. Work-life balance should be improved by improving employees' ability to sort out personal problems from problems encountered in the office. Workloads can be reduced by providing logical task completion targets so as not to overburden employees